BAGAIMANA GAMBARAN PENGGUNAAN ANTIBIOTIK PADA INFEKSI SALUARAN PERNAFASAN AKUT (ISPA) TERHADAP PASIEN RAWAT JALAN DI RUMAH SAKIT TK IV 01.07.01 PEMATANGSIANTAR PERIODE JANUARI-MARET TAHUN 2024 - Ismi Noer Farida; Meyana Marbun, Diyah Ayu Anggriani, Tri Sanjaya (Jurnal Kesehatan, 2025)
What is the description of use of antibiotics in acute respiratory infections (ARI) in outpatients at TK IV Hospital 01.07.01 Pematangsiantar for the period January-March 2024. Introduction;ISPA is a respiratory disease that attacks the upper respiratory and lower respiratory tract,starting from the nose to the lung sacs (alveoli). Method: descriptive research using a retrospective method carried out on past data, namely through medical records of adult ISPA patients. Results; This study shows the percentage results based on gender, the highest number of sufferers is 49 patients (51.04) female with the largest number of women with pneumonia, Namely as many as 28 ISPA patients (29.16 %) 29 use of antibiotics in ISPA patients due to administration of antibiotics.937 levofloxacin were freguently used amoxicillin 16 (66%) azhitromycin 36 patients (36.04 %) (amoxicillin),enterpenemav 17 (17.50) and 18 patients. The conclusion is that more female patients than men are affected by ISPA .the most common ISPA disease is pneumonia, starting at the age of 17-45 years. 500 patients (37.5%) use azitromiycine.